Age-specific trace element bioaccumulation in grey seals from the Gulf of St. Lawrence. (May 2022) - MacMillan, Gwyneth A.; Amyot, Marc; Daoust, Pierre-Yves; Lemire, Mélanie
Abstract: We measured concentrations of 19 trace elements and mercury speciation in grey seals ( Halichoerus grypus ) from the Gulf of St. Lawrence (GSL), Canada. With interest growing in commercializing grey seal products for human consumption in this region, our goal was to measure essential and non-essential trace elements in grey seals to evaluate health concerns and nutritional benefits. From 2015 to 2019, 120 grey seals were sampled by hunters and researchers at 4 sites in the GSL. Muscle, liver, heart and kidney samples were analyzed for 10 non-essential elements (Sb, As, Be, B, Cd, Pb, Hg, Ni, Tl, Sn) and 9 essential elements (Co, Cr, Cu, Fe, Mg, Mn, Mo, Se, Zn). Both total mercury (THg) and methylmercury (MeHg) were analyzed for a subset of samples. Results showed a two-step bioaccumulation pattern with lower element concentrations in the muscle (Fe, Mg, Se) and livers (Cd, Cr, Hg, Mn, Mo, Se) of young-of-the-year harvested in the winter (<6 wks old) compared to older animals feeding at sea. We did not observe progressive age-dependent bioaccumulation for older seals (∼5 mos–29 yrs). Sex-specific differences were not very pronounced, but a few elements were 30–70% higher in the muscle (THg, MeHg) and liver (Mn, Zn) of male seals. Comparison to Canadian dietary reference intakes shows that a weekly portion of liver from young-of-the-year (<6 wks old) is a good source of essential elements (Cu, Fe) and that muscle and liver from this age category do not exceed reference values for toxic elements (As, Cd, Pb, MeHg). Discussions with regional public health professionals are on-going to develop dietary recommendations for the consumption of older grey seals. Graphical abstract: Image 1 Highlights: 19 trace elements and mercury speciation were measured for the first time in grey seals from the Gulf of St. Lawrence. Nutritional benefits and health concerns were evaluated for human consumption of grey seal products. We found a two-step bioaccumulation pattern, with higher concentrations of many elements in seals feeding at sea (> 5 mo). Some elements were more concentrated in the muscle (mercury) and livers (manganese, zinc) of male seals. Muscle and liver tissues from young seals (< 6 we) did not exceed reference values for toxic elements.